Particle shape effects on breakage behaviors in granular materials: a multiscale geotechnical perspective - Bo Liu; Weijun Cen; Guanxi Yan; Alexander Scheuermann; Changhai Zheng; Pei Zhang (Computers and Geotechnics, 2025)

Iron Curtain Formation in Coastal Aquifers: Insights from Darcy-Scale Experiments and Reactive Transport Modelling - Wenran Cao; Harald Hofmann; Alexander Scheuermann (Journal of Marine Science and Engineering, 2025)
Although many studies have examined reaction zones in groundwater–seawater mixing areas, little attention has been given to how subsurface processes drive changes in iron (Fe) precipitation over time and space. This gap has limited our understanding of the “iron curtain” phenomenon in coastal aquifers. To address this, this study developed a reactive transport model to investigate how porosity evolves during the oxidative precipitation of Fe(II) in porous media. The model incorporates the dynamic effects of tortuosity, diffusivity, and surface area as minerals accumulate. Validation experiments, conducted with syringe tests that simulated Fe precipitation during freshwater–saltwater mixing, showed that precipitates formed mainly near the inlets, reflecting the development of a geochemical barrier at the groundwater–seawater interface. Scanning electron microscopy confirmed that Fe precipitates coated the surfaces of spherical particles. Numerical simulations further revealed that high Fe(II) concentrations drove pore clogging near the inlet, creating a dense precipitation zone akin to the iron curtain in coastal aquifers. At 10 mmol/L Fe(II), local clogging was observed, while at 100 mmol/L Fe(II), outflow rates (i.e., discharge) were substantially reduced. Together, the experiments and simulations highlight how hydrogeochemical processes influence hydraulic properties during the oxidative precipitation of Fe(II) in mixing zones.

A machine learning-driven model for predicting macro- and micro-mechanical responses of rockfill materials considering particle breakage - Bo Liu; Weijun Cen; Guanxi Yan; Alexander Scheuermann; Changhai Zheng; Pei Zhang (Computers and Geotechnics, 2025)

Permeability–porosity model considering oxidative precipitation of Fe(II) in granular porous media - Wenran Cao; Nike Hu; Guanxi Yan; Harald Hofmann; Alexander Scheuermann (Journal of Hydrology, 2024)

State of the Art on Fe Precipitation in Porous Media: Hydrogeochemical Processes and Evolving Parameters - Wenran Cao; Guanxi Yan; Harald Hofmann; Alexander Scheuermann (Journal of Marine Science and Engineering, 2024)
The mixing of terrestrial groundwater and seawater creates dynamic reaction zones in intertidal areas, where land-derived Fe(II) is oxidized to Fe(III) and then precipitates as Fe hydroxides at the groundwater–seawater interface. These hydrogeochemical processes contribute to the formation of iron bands at the saltwater wedge (SW) and beneath the upper saline plume (USP). This study provides a comprehensive review of physical and geochemical processes at field scale in coastal areas, explores the impact of mineral precipitation on pore structure at pore scale, and synthesizes reactive transport modeling (RTM) approaches for illustrating continuum-scale soil physio-chemical parameters during the evolution of porous media. Upon this review, knowledge gaps and research needs are identified. Additionally, challenges and opportunities are presented. Therefore, we reach the conclusion that the incorporation of observational data into a comprehensive physico-mathematical model becomes imperative for capturing the pore-scale processes in porous media and their influence on groundwater flow and solute transport at large scales. Additionally, a synergistic approach, integrating pore-scale modeling and non-invasive imaging, is equally essential for providing detailed insights into intricate fluid–pore–solid interactions for future studies, as well as facilitating the development of regional engineering-scale models and physio-chemical coupled models with diverse applications in marine science and engineering.

Porewater exchange and iron transformation in a coastal groundwater system: a field investigation, driving mechanisms analysis, and conceptual model - Wenran Cao; Harald Hofmann; Guanxi Yan; Alexander Scheuermann (Frontiers in Marine Science, 2024)
The high concentration of dissolved iron (Fe) in coastal waters triggers Lyngbya blooms in the Moreton Bay region of Southeast Queensland, Australia. Previous studies have provided a restricted understanding of how land-derived Fe is transported and then transformed into other forms (e.g., Fe oxides) before its release into the ocean. Here, a field investigation was conducted at a sandy beach on the northern end of Deception Bay, Queensland, Australia, focusing on porewater exchange and Fe transformation. This study revealed that tides provided a significant mechanism for driving the groundwater-seawater mixing in the intertidal area. Such forcing formed an upper saline plume (USP) with high dissolved oxygen (DO), creating a dynamic reaction zone for Fe oxidation and precipitation beneath the USP. The spatial distribution of Fe oxides highlighted a substantial Fe content in the subsurface, providing concrete evidence for the transformation of Fe from an aqueous state to a solid form. It also exhibited a low-permeable area that served as a geochemical barrier, absorbing chemical components like phosphate. These findings can assist in constructing a more accurate transport model that couples physical and geochemical processes to quantify the mechanisms driving Fe transformation in coastal areas and further deepen our comprehension of the hydrogeochemical functionalities in land-ocean connectivity via groundwater.

Biological perspectives in geotechnics: theoretical developments - Surabhi Jain; Partha Narayan Mishra; Satyam Tiwari; Yijie Wang; Ningjun Jiang; Hirak Ranjan Dash; Ilhan Chang; Ashutosh Kumar; Sarat Kumar Das; Alexander Scheuermann; Thierry Bore (Reviews in Environmental Science and Bio/Technology, 2023)
The interaction of bio–geosphere dates to the formation of first unicellular microbes on earth. However, it is only relatively recently that the complex biological interactions are observed, characterised, and simulated for its use in the domain of geotechnical engineering. Also, many bioinspired approaches have been utilised in computational geotechnics for optimisation and data analysis process. The living phase present in the soil system hold a bearing on the majority of geochemical reactions and assist in modifying its fundamental and engineering behaviour. It necessitates revaluation and rescrutinisation of the conventional theories and formulations in geotechnical engineering, where soil has always been considered as an inert engineering material from biological perspective. To that end, this manuscript provides a critical review on biological approaches used in geotechnical engineering by highlighting the ongoing developments, achievements, and challenges to implement the processes. The review further emphasises the role of biological systems on the alteration of fundamental properties of soils and their consequences on effective stress, strength and stiffness, volume change and conduction properties of soils. Overall, the manuscript provides a basic understanding on the biological intervention in the soil system and the importance of consideration of the fourth phase in the soil system, i.e., the living phase, while describing such interventions.

The importance of initial particle position on filter performance in granular soils - Samuel Alexander William Holden; Adnan Sufian; Alexander Scheuermann (Computers and Geotechnics, 2023)

Influence of heterogeneity and elevated temperatures on the seismic translational stability of engineered landfills - V. S. Ramakrishna Annapareddy; Anindya Pain; Adnan Sufian; Srikar Godas; Alexander Scheuermann (Waste Management, 2023)

Effects of the Deep Pool on Groundwater Flow and Salinization in Coastal Reservoir and Adjacent Aquifer - Yuming Mo; Guangqiu Jin; Chenming Zhang; Jing Xu; Hongwu Tang; Chengji Shen; Alexander Scheuermann; Ling Li (Water Resources Management, 2021)

Defining a spectrum of integrative trait‐based vegetation canopy structural types - Robert T. Fahey; Jeff W. Atkins; Christopher M. Gough; Brady S. Hardiman; Lucas E. Nave; Jason M. Tallant; Knute J. Nadehoffer; Christoph Vogel; Cynthia M. Scheuermann; Ellen Stuart‐Haëntjens; Lisa T. Haber; Alexander T. Fotis; et al. (Ecology Letters, 2019)
Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning. We use the multivariate structural trait composition of vegetation canopies to classify ecosystems within a global canopy structure spectrum. Across the temperate forest sub‐set of this spectrum, we assess gradients in canopy structural traits, characterise canopy structural types (CST) and evaluate drivers and functional consequences of canopy structural variation. We derive CSTs from multivariate canopy structure data, illustrating variation along three primary structural axes and resolution into six largely distinct and functionally relevant CSTs. Our results illustrate that within‐ecosystem successional processes and disturbance legacies can produce variation in canopy structure similar to that associated with sub‐continental variation in forest types and eco‐climatic zones. The potential to classify ecosystems into CSTs based on suites of structural traits represents an important advance in understanding and modelling structure–function relationships in vegetated ecosystems.

Pore-Scale Simulations of Simultaneous Steady-State Two-Phase Flow Dynamics Using a Lattice Boltzmann Model: Interfacial Area, Capillary Pressure and Relative Permeability - Zi Li; Sergio Galindo-Torres; Guanxi Yan; Alexander Scheuermann; Ling Li (Transport in Porous Media, 2019)

Nutzen von Feuchtemessungen mittels TDR zur Beurteilung von Strömungsvorgängen in Dämmen und Deichen - Alexander Scheuermann; Andreas Bieberstein (WASSERWIRTSCHAFT, 2006)